Highly-immunogenic virally-vectored T-cell vaccines cannot overcome subversion of the T-cell response by HCV during chronic infection - Swadling, L; Halliday, J; Kelly, C; Brown, A; Capone, S; Ansari, M; Bonsall, D; Richardson, R; Hartnell, F; Collier, J; Ammendola, V; Del Sorbo, M; et al. (MDPI, 2016)
An effective therapeutic vaccine for the treatment of chronic hepatitis C virus (HCV) infection, as an adjunct to newly developed directly-acting antivirals (DAA), or for the prevention of reinfection, would significantly reduce the global burden of disease associated with chronic HCV infection. A recombinant chimpanzee adenoviral (ChAd3) vector and a modified vaccinia Ankara (MVA), encoding the non-structural proteins of HCV (NSmut), used in a heterologous prime/boost regimen induced multi-specific, high-magnitude, durable HCV-specific CD4+ and CD8+ T-cell responses in healthy volunteers, and was more immunogenic than a heterologous Ad regimen. We now assess the immunogenicity of this vaccine regimen in HCV infected patients (including patients with a low viral load suppressed with interferon/ribavirin therapy), determine T-cell cross-reactivity to endogenous virus, and compare immunogenicity with that observed previously in both healthy volunteers and in HCV infected patients vaccinated with the heterologous Ad regimen. Vaccination of HCV infected patients with ChAd3-NSmut/MVA-NSmut was well tolerated. Vaccine-induced HCV-specific T-cell responses were detected in 8/12 patients; however, CD4+ T-cell responses were rarely detected, and the overall magnitude of HCV-specific T-cell responses was markedly reduced when compared to vaccinated healthy volunteers. Furthermore, HCV-specific cells had a distinct partially-functional phenotype (lower expression of activation markers, granzyme B, and TNFα production, weaker in vitro proliferation, and higher Tim3 expression, with comparable Tbet and Eomes expression) compared to healthy volunteers. Robust anti-vector T-cells and antibodies were induced, showing that there is no global defect in immunity. The level of viremia at the time of vaccination did not correlate with the magnitude of the vaccine-induced T-cell response. Full-length, next-generation sequencing of the circulating virus demonstrated that T-cells were only induced by vaccination when there was a sequence mismatch between the autologous virus and the vaccine immunogen. However, these T-cells were not cross-reactive with the endogenous viral variant epitopes. Conversely, when there was complete homology between the immunogen and circulating virus at a given epitope T-cells were not induced. T-cell induction following vaccination had no significant impact on HCV viral load. In vitro T-cell culture experiments identified the presence of T-cells at baseline that could be expanded by vaccination; thus, HCV-specific T-cells may have been expanded from pre-existing low-level memory T-cell populations that had been exposed to HCV antigens during natural infection, explaining the partial T-cell dysfunction. In conclusion, vaccination with ChAd3-NSmut and MVA-NSmut prime/boost, a potent vaccine regimen previously optimized in healthy volunteers was unable to reconstitute HCV-specific T-cell immunity in HCV infected patients. This highlights the major challenge of overcoming T-cell exhaustion in the context of persistent antigen exposure.